Cumulative effects of genetic markers and the detection of advanced colorectal neoplasias by population screening. (30th October 2014) - Kurlapska, A.; Serrano‐Fernández, P.; Baszuk, P.; Gupta, S.; Starzyńska, T.; Małecka‐Panas, E.; Dabrowski, A.; Dębniak, T.; Kurzawski, G.; Suchy, J.; Rogoza‐Mateja, W.; Scott, R.J.; et al.
<x xml:space="preserve">Abstract</x> Genetic markers associated with colorectal cancer may be used in population screening for the early identification of patients at elevated risk of disease. We genotyped 3059 individuals with no cancer family history for eight markers previously associated with colorectal cancer. After colonoscopy, the genetic profile of cases with advanced colorectal neoplasia (213) was compared with the rest (2846). rs2066847 and rs6983267 were significantly associated with the risk of advanced colorectal neoplasia but with limited effect on their own [odds ratio (OR) 1.59; 95% confidence interval (CI) 1.02–2.41; p = 0.033 and OR 1.45; 95% CI 1.02–2.12; p = 0.044, respectively]. Cumulative effects, in contrast, were associated with high risk: the combination of rs2066847, rs6983267, rs4779584, rs3802842 and rs4939827 minimized the number of markers considered, while maximizing the relative size of the carrier group and the risk associated to it, for example, for at least two cumulated risk markers, OR is 2.57 (95% CI 1.50–4.71; corrected p‐value 0.0079) and for three or more, OR is 3.57 (95% CI 1.91–6.96; corrected p‐value 0.00074). The identification of cumulative models of – otherwise – low‐risk markers could be valuable in defining risk groups, within an otherwise low‐risk population (no cancer family history).